Penggunaan Delone And Mclean Dalam Mengevaluasi Kesuksesan Sistem Informasi Terhadap E-Ppt Fakultas Ilmu Komputer Universitas Sriwijaya - Salsabila, Adella; Yunika Hardiyanti, Dinna (Jurnal Algoritma, 2025)
The e-PPT system of the Faculty of Computer Science Universitas Sriwijaya was developed to support online academic administrative services. However, based on observations, users sometimes experience problems such as connection interruptions, a user interface that is not user friendly, and delays in document processing. This study aims to evaluate the success of the e-PPT system implementation using the DeLone and McLean 2003 model with a quantitative approach based on Partial Least Squares Structural Equation Modeling PLS SEM. Data were collected from 353 active students through an online questionnaire, measuring six dimensions namely system quality, information quality, service quality, use, user satisfaction, and net benefits. The results show that information quality and service quality have a significant influence on use and user satisfaction, with service quality being the main driver of system use path coefficient 0.416. Service quality is significant for user satisfaction but not for use p value 0.081. Both use and user satisfaction contribute significantly to net benefits such as time and cost savings. Although the validity and reliability of the instruments were confirmed AVE greater than 0.5 and Cronbachs Alpha greater than 0.7, weaknesses in service quality such as connection errors and a less user friendly interface still need improvement. This study recommends improving administrative responsiveness, simplifying the interface, and adding qualitative analysis for deeper contextual understanding. These findings are relevant for developing more effective academic information systems in higher education institutions.